Linking Tourism and Conservation Awareness: A Case Study from Raja Ampat, Indonesia - Rima Herlina Setiawati Siburian; Maryrose Easter Tapilatu; Julia Rosemary Tapilatu (Marine Science Department Diponegoro University, 2026)
Raja Ampat is one of the most visited destinations by tourists to experience marine biodiversity, including sharks. Shark related tourism is one of the fastest growing tourisms and it can provide an engaging experience as well as improving public attitudes and raising awareness of shark conservation. In this case, this study assesses the knowledge and experience gained by tourists visiting Kri Island (Raja Ampat) while participating in shark related tourism. The study was conducted from August to October 2024 by interviewing 200 respondents. The assessment was carried out by implementing semi-structured interviews, with a qualitative-quantitative approach to assess tourist motivation and the outcomes after participating in the shark related activity program. This study also examines the extent to which education obtained from shark tourism experiences can contribute to tourist attitudes that supports shark conservation efforts in Raja Ampat. Based on a comparative analysis between pre- and post-activity surveys of 200 tourists showed a positive change in tourist perceptions of sharks after participating in these activities. The results of our finding indicate that providing education during shark-based activities can have a significant impact on conservation that will help in maintaining the ecological status of shark species that are currently endangered. Overall, we conclude that with interpretive encounters, shark-based tourism can provide significant benefits by increasing tourist satisfaction and encouraging attitudes that support conservation.